Dataset ice nucleating activity of Arctic sea surface microlayer samples and marine algal cultures ... - Ickes, Luisa; Porter, Grace C. E.; Wagner, Robert; Adams, Michael P.; Bierbauer, Sascha; Christiansen, Sigurd; Höhler, Kristina; Schiebel, Thea; Ullrich, Romy; Salter, Matthew (Karlsruhe Institute of Technology, 2023)
This dataset contains all the measurements used for the analysis of the respective publication. More details on the measurement setup etc. can be found in there. The data contains of three subfolders, one including the AIDA data, one the INKA and one the mul-NIPI data. Each folder contains one txt file for each experiment of the measurement campaign (see Table 2 in the publication). The name of the txt file represents the sample and the aerosolisation technique used (in case of the AIDA and INKA data). Below we give a short explanation on the data in each folder: AIDA: Each data file consists of 6 columns: temperature T ([T]=K), the uncertainty of T deltaT, the surface active site density nS ([ns]=m-2), the uncertainty of ns deltanS, the ice nucleation active site density per mass of sea salt nm ([nm]=g-1), the uncertainty of nm deltanm. The AIDA ns data were corrected for the background ice nucleation mode observed in the reference experiments with purely inorganic Sigma-Aldrich sea salt solution droplets ...